Estimation of functional preparedness of young handballers in setup time - Favoritоv V.N; Dyadechko I.E; Melnik T.V (Kharkov National Pedagogical University, 2012)
The dynamics of level of functional preparedness of young handballers in setup time is shown. It was foreseen to make alteration in educational-training process with the purpose of optimization of their functional preparedness. 11 youths were plugged in research, calendar age 14 - 15 years. For determination of level of their functional preparedness the computer program "SVSM" was applied. It is set that at the beginning of setup time of 18,18% of all respondent functional preparedness is characterized by a "middle" level, 27,27% - below the "average", 54,54% - "above" the average. At the end of setup time among sportsmen representatives prevailed with the level of functional preparedness "above" average - 63,63%, with level "high" - 27,27%, sportsmen with level below the average were not observed. Efficiency of the offered system of trainings employments for optimization of functional preparedness of young handballers is well-proven.